PENGARUH SEMANGAT DAN DISIPLIN KERJA TERHADAP KINERJA GURU (Studi Pada Guru SMPN 1 Taliwang Kabupaten Sumbawa Barat) - K Kurniawansyah; Ulfa Yuniar; Abdul Rahim (Fakultas Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the effect of morale and work discipline on teacher performance at SMPN 1 Taliwang, West Sumbawa Regency. The population in this study were all teachers at SMPN 1 Taliwang, West Sumbawa Regency, totaling 32 people. The researchers took the entire population to be used as a research sample (census sampling). Data in the study were collected through questionnaires distributed to research respondents and analyzed using simple linear regression analysis techniques, individual parameter hypothesis testing (t-test), simultaneous parameter hypothesis testing (F-test), and determinant coefficient test (R2). The results of this study indicate that work enthusiasm and work discipline have a positive and significant effect on teacher performance at SMPN 1 Taliwang, West Sumbawa Regency, both partially and simultaneously. The degree of influence of work enthusiasm and work discipline on teacher performance at SMPN 1 Taliwang, West Sumbawa Regency is 89.1%, while the remaining 10.9% is influenced by other variables outside this research model, such as the work environment, principal leadership patterns and others.